Presence of Streptococcus dentisani in the dental plaque of children from different Colombian cities (2019)
Streptococcus dentisani has been identified as an oral cavity probiotic due to its beneficial characteristics. One of its beneficial features is the production of bacteriocins, which inhibit the growth of cariogenic bacteria, and another is its buffering capacity through the production of ammonium from arginine. The purpose of this study was to determine the presence of S. dentisani in the dental plaque of Colombian children and whether the presence of this bacterium is related to oral health and other conditions. Dental plaque and information on diet and oral hygiene habits were collected from children between 6 and 12 years of age from four Colombian cities, divided into caries‐free children (International Caries Detection and Assessment System [ICDAS] 0, Decayed Missing Filled Teeth index [DMFT] 0), children with ICDAS 1 and 2, and children with ICDAS >3. Plaque DNA was extracted and quantified, and real‐time polymerase chain reaction was performed using specific primers. This bacterium was identified in all samples, with a median of 0.46 cells/ng DNA (interquartile range [IQR] 0.13–1.02), without finding significant differences between the groups (P > 0.05). In caries‐free children, a median of 0.45 cells/ng DNA (IQR 0.14–1.23) was found. In children with ICDAS 1 and 2, the median was 0.49 cells/ng DNA (IQR 0.11–0.97), and in children with ICDAS >3, the median was 0.35 cells/ng DNA (IQR 0.12–1.07). However, statistically significant differences were found in the origin of children (P < 0.01), the use of fluoride‐containing products (P < 0.01), and the frequency of food intake (P < 0.05). In conclusion, the presence of S. dentisani was quantified in children from four Colombian cities, without finding significant differences in oral health status. Nevertheless, three conditions showed a possible relationship with S. dentisani.